THE IMPLEMENTATION OF THE HERRINGBONE TECHNIQUE IN READING NARRATIVE TEXT - Humairah, Humairah; Sakkir, Geminastiti; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study aims to determine the increase in students' reading comprehension of narrative texts after applying the herringbone technique. This study a quantitative method. To achieve the research objectives, this study used an instrument in the form of a reading comprehension test. The population of this study was all class XI students at SMA Negeri 7 Pinrang, totaling 244 students from 7 different classes, in the odd semester of the 2023–2024 academic year. The interview sample was 34 students in class XI F of SMA Negeri 7 Pinrang, in the odd semester of the 2023–2024 academic year. As a result of the data analysis carried out, researchers can conclude that the application of the herringbone technique in reading can improve students' reading comprehension in narrative texts at SMA Negeri 7 Pinrang.